DEVELOPMENT OF DISCOVERY LEARNING-ORIENTED PHYSICS E-MODULES FOR STUDENTS OF CLASS X MIPA CHAPTER WORK AND ENERGY (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2021)
The purpose of this research is to develop teaching materials in the form of a Discovery Learning-oriented physics learning module that is valid and practical for students of class X SMA science program. This type of research uses Research and Development (R&D). The research subjects of class X MIPA 5 were 39 people. The research procedure used by the 4-D model is definition, design, development and dissemination. The research instrument is a questionnaire of initial analysis, validity, and practicality. Furthermore, the data were analyzed to see the validity and practicality of the E-module. E-module validation is assessed from the aspect of ease of use, time required, easy to interpret, and has the same equivalence. The results showed that the E-physics module was categorized as very valid with a percentage of 91.96%. Furthermore, the practicality of the E-module is assessed from the aspect of ease of use, time required, easy to interpret, and has the same equivalence with a percentage of 92.77%.Keywords: Discovery Learning, E-module physics